"Our job is to break that chain of infection": Challenges environmental management services (EMS) staff face in accomplishing their critical role in infection prevention - Cassie Cunningham Goedken; Linda McKinley; Erin Balkenende; Stacey Hockett Sherlock; Mary Jo Knobloch; Eli N. Perencevich; Nasia Safdar; Heather Schacht Reisinger (Cambridge University Press, 2022)
Abstract Objectives: Contaminated surfaces in healthcare settings contribute to the transmission of nosocomial pathogens. Adequate environmental cleaning is important for preventing the transmission of important pathogens and reducing healthcare-associated infections. However, effective cleaning practices vary considerably. We examined environmental management services (EMS) staff experiences and perceptions surrounding environmental cleaning to describe perceived challenges and ideas to promote an effective environmental services program. Design: Qualitative study. Participants: Frontline EMS staff. Methods: From January to June 2019, we conducted individual semistructured interviews with key stakeholders (ie, EMS staff) at 3 facilities within the Veterans' Affairs Healthcare System. We used the Systems Engineering Initiative for Patient Safety (SEIPS) framework (ie, people, environment, organization, tasks, tools) to guide this study. Interviews were audio-recorded, transcribed, and analyzed for thematic content. Results: In total, 13 EMS staff and supervisors were interviewed. A predominant theme that emerged were the challenges EMS staff saw as hindering their ability to be effective at their jobs. EMS staff interviewed felt they understand their job requirements and are dedicated to their work; however, they described challenges related to feeling undervalued and staffing issues. Conclusions: EMS staff play a critical role in infection prevention in healthcare settings. However, some do not believe their role is recognized or valued by the larger healthcare team and leadership. EMS staff provided ideas for improving feelings of value and job satisfaction, including higher pay, opportunities for certifications and advancement, as well as collaboration or integration with the larger healthcare team. Healthcare organizations should focus on utilizing these suggestions to improve the EMS work climate.